Brain abscess secondary to frontal osteomyelitis Abscesso cerebral secundário à osteomielite frontal - Felipe Francisco Tuon; Rachel Russo; Antonio Carlos Nicodemo (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
Frontal osteomyelitis is a rare complication of sinusitis. Common intracranial complications of the frontal osteomyelitis are meningitis, epidural empyema, subdural empyema and brain abscess. We described a case of frontal osteomyelitis with brain abscess caused by Staphylococcus aureus with improve after needle aspiration and antibiotics to brain abscess for eight weeks and for chronic osteomyelitis for four months. A osteomielite de osso frontal é uma complicação rara da sinusite frontal. As complicações intracranianas mais comuns da osteomielite frontal são: meningite, empiema epidural, empiema subdural e abscesso cerebral. Relatamos um caso de osteomielite frontal com abscesso cerebral cujo agente etiológico foi o Staphylococcus aureus. Houve melhora significativa após drenagem guiada por agulha e antibiótico por oito semanas e para a osteomielite crônica por quatro meses.